Characteristics of Wooden Furniture Drying Machine - Petrus Kanisius Purwadi; A. Prasetyadi (Universitas Sanata Dharma, 2022)
This study aims to determine the characteristics of the electric energy drying machine used to dry wooden furniture. Furniture made of mahogany. The research was conducted experimentally in the wood furniture industry. The size of the wood drying room is 8 m x 6 m x 3 m. The dryer works with a vapor compression cycle using R134a freon and several fans placed in the drying chamber. The drying process uses a closed air system. The total volume of dried wooden furniture is 12.9 m3. The initial moisture content in the wood ranges from 18% to 23%. Wooden furniture is considered dry if the moisture content in the wood furniture is less than 12%. Research gives satisfactory results. The performance of the drying machine or COP is 10.85. The drying time for wooden furniture is about 72 hours.